Nexus of Foreign Direct Investment, Domestic Investment, and Manufacturing Industry Value Added in Indonesia - Horas Djulius; Choi Wongyu; J. Juanim; Raeni Dwi Santy (Signifikan: Jurnal Ilmu Ekonomi, 2019)
The development of the manufacturing industry is one of the standards for Indonesia's development as a developing country. Domestic investment (DI) and foreign direct investment (FDI) can meet investment needs in this industry. This paper focuses on the nexus of the two types of investment in meeting investment needs in the manufacturing industry and the influence of those investments in relatively capital-intensive and relatively labor-intensive industrial groups. The aim is to evaluate the role of both types of investments and their benefits to the economy not only to the value-added but also in transferring technology and knowledge spillover from FDI to DI. The panel data regression was first to do to observe the differences between groups of relatively capital-intensive industrial samples and relatively labor-intensive industrial samples. The comparison results show that there are significant differences between the two industry groups so that it can be regressed on these two sample types, apart from the regression of the overall sample. The overall sample found that both FDI and DI influence the value-added of the manufacturing industry.